2016
DOI: 10.1021/acs.molpharmaceut.6b00532
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Profiles and Intestinal Toxicity Assessment of Hydrochlorothiazide and Its Inclusion Complex with β-Cyclodextrin Loaded into Chitosan Nanoparticles

Abstract: Here, a novel drug delivery system was developed for the hydrochlorothiazide (HCT):β-cyclodextrin (βCD) inclusion complex loaded into chitosan (CS) nanoparticles (NPs) [CS/HCT:βCD NPs]. It was found, for the first time, that exposure of the intestinal mucosa to free HCT resulted in an increased and abnormal intestinal permeability associated with several injuries to the intestinal epithelium. Nevertheless, the HCT delivery system obtained ameliorated the damage of the intestinal epithelium induced by HCT. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…No toxicity or structural damage was detected in any of the ex vivo studies ( Onnainty et al, 2016 ; Shah et al, 2016 ; Wardani et al, 2018 ; Tzeyung et al, 2019 ). One of them demonstrated that an active ingredient (hydrochlorothiazid) became less toxic when incorporated into chitosan nanoparticles, compared to the free form ( Onnainty et al, 2016 ), and another study showed that chitosan nanoparticles exhibited a protective effect against free radicals ( Wardani et al, 2018 ). An in vivo study in mice demonstrated that the chitosan nanoparticles were well tolerated, as no inflammation or pathological changes were detected ( Sonaje et al, 2009 ).…”
Section: Results Of Cytotoxicity Measurements On Chitosan Containing ...mentioning
confidence: 85%
See 1 more Smart Citation
“…No toxicity or structural damage was detected in any of the ex vivo studies ( Onnainty et al, 2016 ; Shah et al, 2016 ; Wardani et al, 2018 ; Tzeyung et al, 2019 ). One of them demonstrated that an active ingredient (hydrochlorothiazid) became less toxic when incorporated into chitosan nanoparticles, compared to the free form ( Onnainty et al, 2016 ), and another study showed that chitosan nanoparticles exhibited a protective effect against free radicals ( Wardani et al, 2018 ). An in vivo study in mice demonstrated that the chitosan nanoparticles were well tolerated, as no inflammation or pathological changes were detected ( Sonaje et al, 2009 ).…”
Section: Results Of Cytotoxicity Measurements On Chitosan Containing ...mentioning
confidence: 85%
“…Several of the papers demonstrated that chitosan in nanoparticle form was less cytotoxic than chitosan in free form ( Amidi et al, 2006 ; Yin et al, 2009 ; Pistone et al, 2017b ; Facchinatto et al, 2021 ). The active ingredient (clotrimazole and hydrochlorothiazide) also showed less cytotoxicity when incorporated in chitosan nanoparticles ( Onnainty et al, 2016 ; Facchinatto et al, 2021 ). Reduced toxicity of the active ingredient (Centella asiatica) was also seen after incorporation into chitosan nanoparticles ex vivo ( Haroon et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reported aqueous solubility is 0.7 g/L, and logP – 0.07 . HCT is reported as a BCS class IV drug in a number of reports. However, according to the WHO essential medicine list, BCS is a class III drug . Sanphui et al reported five cocrystals of HCT, and their solubility and permeability properties were extensively studied .…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal permeation of HCT was studied by applying the everted rat gut sac technique (Onnainty et al, ; Quevedo & Briñón, ; Quevedo, Nieto, & Briñón, ; Raposo, ). The medium was TC199, pH 7.4, and with 95% O 2 –5% CO 2 gas bubbling at 37°C.…”
Section: Methodsmentioning
confidence: 99%